Bacterial cellulose and silk fibroin biopolymers: biotemplates to design nanostructured materials for optical applications - Santos, Molíria Vieira dos [UNESP] (2016)
Among all natural polymers, bacterial cellulose and silk fibroin offer unlimited opportunities for processing, functionalization, and biological integration. This thesis presents the preparation and characterization of nanostructured materials based on bacterial cellulose produced by Gluconacetobacter xylinus bacteria, as well as regenerated silk fibroin stemmed from the cocoons of silkworms (Bombyx mori) for optical applications. Firstly, dried bacterial cellulose membranes were utilized to prepare cellulose nanocrystals (CNC). CNC were casted in the form of thick iridescent films whose color originates in the periodic patterning of layers in a chiral nematic texture created by self-assembly of rod crystallites. Once the CNC films were obtained, self-sustainable films were coated with a low molecular weight nematic liquid crystal (LC), 4′-(hexyloxy)-4-biphenylcarbonitrile (HOBC). The materials were obtained as free-standing iridescent films, with chiral nematic structure that exhibited modulated optical properties, in response to external stimulus, such as thermal gradient or relatively small electrical voltage. The scanning electron microscopy (SEM) confirmed that the composite film structure comprises the multi-domain Bragg reflectors. The relationship between the surface structure and thermo-responsive properties of investigated HOBC coated with CNC film was examined using transmission optical microscopy (TOM). Additionally, electrostatic force microscopy (EFM) measurement was employed to prove the effect of external stimuli, in this case applied voltage, on the HOBC liquid crystal coated with CNC film. The second part of this thesis involves the design of luminescent iridescent films through the combination of CNC suspension with tetraethoxysilane (TEOS) and ethanolic solutions of Rhodamine 6G (Rh6G). These materials were obtained as freestanding composite films with chiral nematic organization. The optical properties of such films can be tuned through changes in the silica/CNC proportion during the preparations. Photoluminescence measurements, as function of the detection angle, were realized in order to investigate the influence of photonic structure in the light emission of composite films. Our findings demonstrated that the photonic structure of the film acts as an inner- filter, causing selective suppression of the light emitted with a variation of the detection angle. This behavior was found to be dependent of the bandgap position on the photonic structure of these materials. Lastly, we designed structured organic-inorganic hybrids (OIH) based on silica and silk fibroin. The materials were obtained as robust monoliths possessing different fibroin fractions. The SEM images demonstrated in-situ self-assembly of fibroin nanofibers dispersed into the IOH monoliths. Structural characterization of OIH monoliths was performed by Raman and solid state NMR spectroscopies. Our findings demonstrated that precipitated fibroin presented prevailing β-sheet conformation. Furthermore, we demonstrated that the fibroin nanofibers can be used as biotemplates, acting as a sacrificial material to development porous silica monoliths. The porous silica monoliths doped with rhodamine 6g (Rh6G) exhibited efﬁcient RL action with low threshold power excitation and narrowing linewidth. From the spectral behavior, it is inferred that the RL operates in the diffusive regime in hierarchical macro–mesoporous network. In addition, analysis of the emission spectra showed two gain mechanisms coupled, specifically the random lasing and the stimulated Raman scattering, which suggest that designed materials can also be promising for random Raman laser applications.